Сто> великих скульпторов: энциклопедия / авт. С. А. Мусский - Мусский С. А. (100 великих, 2002)
Экземпляры: Д.О. (20231108) / Инвентарный номер: 50120 / Цена: 120.00 / Авт.знак: С 81 / ББК: 85.133(3)я20